Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am trying to understand the definition of a logarithm, because when I was trying to find the derivative of $2^x$ I got $$2^x \lim_{h \to 0} \frac{2^h-1}{h}$$ which I have found by searching to be $\ln(2)$. I did get a bit confused because I would need to use l'hopital rule, which would bring be back to what I was trying to find.

But my question that I think I need to understand before getting to my second question.

Euler defines logarithm as $$\ln(x)=\lim_{n \to \infty}n(x^{\tfrac{1}{n}}-1)$$

Which then must be equal to $$\ln(x)=\lim_{h \to 0} \frac{x^h-1}{h} $$

Could you help me understand how these are both the same?

share|improve this question
    
I'm not sure how Euler defined logarithm, but $\lim \limits_{n \rightarrow \infty} n(x^{\frac{1}{2}} - 1)$ is clearly not right as it is $\pm \infty$ for $x \neq 1$. It was probably $\lim \limits_{n \rightarrow \infty} n(x^{\frac{1}{n}} - 1)$. –  Karolis Juodelė Sep 9 '12 at 11:43
    
@KarolisJuodelė you are correct, I edit it to fix that. –  yiyi Sep 9 '12 at 13:52
    
I posted this related answer here recently. –  Michael Hardy Sep 9 '12 at 18:57

2 Answers 2

up vote 2 down vote accepted

These are both the same since if you define $h = 1/n$, you get your second equation from the first.

share|improve this answer

If you are trying to find the derivative of $2^x$ then you also can do it using the property of $e$

$$ \lim_{h \to 0} \frac{2^h-1}{h} = \lim_{h \to 0} \frac{e^{\ln(2) h}-1}{h \ln (2)}\times \ln(2) = \ln (2) \times 1 = \ln(2)$$

share|improve this answer
1  
The problem here is that the limit appeared trying to find the derivative of $2^x$, which means using l'Hopital would get you into a circular argument. Trivia: You get into the same pickle when differentiating $\sin (x)$. –  Arthur Sep 9 '12 at 12:03
    
@Arthur $$\frac{d}{dx}sin(x) = \lim_{h\to\infty} \frac{sin(x+h)-sin(x)}{h}$$ $$=\lim_{h\to\infty} \frac{sin(x)cos(h)+cos(x)(sin(h)-sin(x)}{h}$$ $$\because sin(x+h)=sin(x)cos(h)+cos(x)sin(h)$$ $$ =\lim_{h\to\infty}\frac{sin(x)(cos(h)-1)+cos(x)sin(h)}{h}$$ $$=\lim_{h\to\infty} sin(x)\frac{cos(h)-1}{h} + \lim_{h\to\infty} cos(x)\frac{sin(h)}{h} $$ $$ \frac{d}{dx}sin(x)=sin(x)(0) + cos(x)(1) = cos(x)$$ –  yiyi Sep 9 '12 at 14:05
1  
@MaoYiyi First off, I think you mean $h\to 0$. Then I would like to point your attention towards the limit $$\lim_{h\to0} \cos(x)\frac{\sin(h)}{h}$$ in which one might use l'Hopital since that's easiest, without considering the circular argument. –  Arthur Sep 9 '12 at 15:49
    
@Arthur thanks alot –  yiyi Sep 9 '12 at 16:25

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.